2023
DOI: 10.14740/gr1622
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasitic Infections in 2023

Abstract: Intestinal parasites include intestinal protozoa and intestinal helminths. Intestinal parasitic infections (IPIs) pose a global health problem affecting over one billion people worldwide. Although these infections are predominantly seen in the developing world, they are frequently seen in the developed countries, particularly in immunocompromised patients. Patients’ clinical presentations generally include diarrhea, dysentery, abdominal pain, nausea, vomiting, nutritional deficiency, iron deficiency anemia, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Infections are widespread in tropical and subtropical areas, with the highest numbers occurring in sub-Saharan Africa, the Americas, and Asia [15]. According to studies, the prevalence of IPIs in Africa ranges from 6.6% -86% [4,16]. The present study, which was conducted in northern Madagascar, found that 71.0% of the participants were infected with intestinal parasites, and that 27% of those infections were caused by pathogenic parasites (5.8% helminthic and 21.2% protozoan infections), and 48.5% by the potentially pathogenic stramenopila.…”
Section: Discussionmentioning
confidence: 99%
“…Infections are widespread in tropical and subtropical areas, with the highest numbers occurring in sub-Saharan Africa, the Americas, and Asia [15]. According to studies, the prevalence of IPIs in Africa ranges from 6.6% -86% [4,16]. The present study, which was conducted in northern Madagascar, found that 71.0% of the participants were infected with intestinal parasites, and that 27% of those infections were caused by pathogenic parasites (5.8% helminthic and 21.2% protozoan infections), and 48.5% by the potentially pathogenic stramenopila.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent intestinal protozoa transmitted through polluted water are E. histolytica and G. lamblia. Their cysts pollute the environment and water systems as well and can withstand environmentally harsh conditions, e.g., G. lamblia can survive at 21 °C for a month (Ahmed, 2023). Endolimax nana and Entamoeba coli are not harmful, although they can be indicators of fecal contamination in the environment.…”
Section: Mode Of Transmissionmentioning
confidence: 99%
“…Soil-transmitted helminths (STHs), also referred to as geohelminths, primarily afflict children who live in extreme poverty and predominantly also those who live in rural areas or communities with a lack of water, poor hygiene and low education [ 1 , 23 , 18 ]. Although patients with low-intensity infections caused by STHs may be asymptomatic, moderate- to high-intensity infections are associated with gastrointestinal symptoms, anaemia, as well as deterioration of the physical development of children [ 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ascaris lumbricoides is the most frequent nematode infecting the small intestine of humans with a cosmopolitan distribution. Ascariasis is the most common helminthiasis in the world and occurs primarily in sub-Saharan Africa, Latin America, China and the Indian subcontinent [ 2 , 18 , 23 ]. Ascariasis negatively affects the nutrition and cognitive development of preschool and school children [ 2 , 24 , 25 ]; the most vulnerable group comprises preschool-aged children [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation